A diketopyrrolopyrrole-based dimer as a blue pigment - Casutt, Manuela; Kushida, Soh; Bunz, Uwe H. F.; Freudenberg, Jan; Jänsch, Daniel (Chemistry - a European journal, 2019)
1,4-Diketopyrrolo[3,4-c]pyrroles (DPPs) constitute a class of hydrogen-bonded pigments covering a color range from yellow-orange to dark violet. We report facile dimerization of a Boc-substituted 3,6-dithienyl-DPP. The formed dimer shows brilliantly blue color as a result of the expansion of the chromophore. The soluble dimer acts as latent pigment and is converted to the corresponding pigment either via thermocleavage or acidic deprotection of the Boc groups. The synthesized pigment is characterized by high migrational stability in a polymer matrix and a clear blue color.